Agriculture for Improved Nutrition: Seizing the Momentum 2019
DOI: 10.1079/9781786399311.0001
|View full text |Cite
|
Sign up to set email alerts
|

Seizing the momentum to reshape agriculture for nutrition.

Abstract: A man delivers milk in Nepal. Low milk production has prompted the government to import fresh milk from India in order to meet demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Further, the results were in line with Brown and Westaway [11], specifically in terms of their findings when measuring community resilience to environmental change for community well-being and disaster recovery. This empirical evidence, consistent with Sanginga et al [44], and Fan, Yosef and Pandya-Lorch [43], used innovation to sustain farming, while Milestad and Darnhofer [47] found that learning and adaptation to the climate change is an integral part of community resilience. In summary, all of the above-mentioned dimensions support the FCR model.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Further, the results were in line with Brown and Westaway [11], specifically in terms of their findings when measuring community resilience to environmental change for community well-being and disaster recovery. This empirical evidence, consistent with Sanginga et al [44], and Fan, Yosef and Pandya-Lorch [43], used innovation to sustain farming, while Milestad and Darnhofer [47] found that learning and adaptation to the climate change is an integral part of community resilience. In summary, all of the above-mentioned dimensions support the FCR model.…”
Section: Discussionsupporting
confidence: 86%
“…The economic dimensions have also been confirmed by previous researchers, such as [48], in terms of the integration of a "system-of-systems" that includes physical, social, and economic aspects for sustainable community resilience. Similarly, the environmental, community competence, and information and communication dimensions, as indicated by previous researchers, are essential strategies for strengthening the resilience of community [11,18,38,43]. This study integrated the different ideas of previous researchers and empirically verified them with statistical procedures.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The implementation of teff as an advantageous staple food crop is rapidly growing due to its relative ease of cultivation, sensory quality of teff-based products, and favorable macro- and micronutrient composition [ 3 , 18 , 27 ]. Compared to other crops, teff does contain notable antinutrients, such as a higher concentration of phytic acid; however, processing methods such as fermentation can drastically lower phytic acid concentration and thus mineral inaccessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in Asia, but increasingly for the rest of the developing world, diets are shifting away from staples and toward livestock and dairy products, vegetables and fruits, and fats and oils. As income in both rural and urban areas increases, demand for more diversified foods is increasing and agricultural production in turn is driven by the demand to further diversify its products, which contribute to more-balanced diets (Fan, Yosef, and Pandya-Lorch 2019a).…”
Section: The Dietary Transitionmentioning
confidence: 99%